Rapid detection of green-pea adulteration in pistachio nuts using Raman spectroscopy and chemometrics - Taylan, Osman; Cebi, Nur; Yilmaz, Mustafa Tahsin; Sagdic, Osman; Ozdemir, Durmus; Balubaid, Mohammed (WILEY, 2021)
BACKGROUND Ground pistachio nut is prone to adulteration because of its high economic value and wide usage. Green pea is known as the main adulterant in frauds involving pistachio nuts. The present study developed a new, rapid, reliable and low-cost methodology by using a portable Raman spectrometer in combination with chemometrics for the detection of green pea in pistachio nuts. RESULTS Three different methods of Raman spectroscopy-based chemometrics analysis were developed for the determination of green-pea adulteration in pistachio nuts. The first method involved the development of hierarchical cluster analysis (HCA) and principal component analysis (PCA), which differentiated authentic pistachio nuts from green pea and green pea-adulterated samples. The best classification pattern was observed in the adulteration range of 20-80% (w/w). In addition to classification methods, partial least squares regression (PLSR) and genetic algorithm-based inverse least squares (GILS) were also used to develop multivariate calibration models to determine quantitatively the degree of green-pea adulteration in grounded pistachio nuts. The spectral range of 1790-283 cm(-1)was used in the case of multivariate data analysis. A green-pea adulteration level of 5-80% (w/w) was successfully identified by PLSR and GILS. The correlation coefficient of determination (R-2) was determined as 0.91 and 0.94 for the PLSR and GILS analyses, respectively. CONCLUSION A Raman spectrometer combined with chemometrics has a high capability with regard to the detection of adulteration in pistachio nuts, combined with low cost, strong reliability, a high level of accuracy, rapidity of analysis, and minimum sample preparation.
Keywords: portable Raman; pistachio nut; hierarchical cluster analysis (HCA); principal component analysis (PCA); partial least squares (PLSR); genetic inverse least squares (GILS); FOURIER-TRANSFORM RAMAN; INFRARED-SPECTROSCOPY; HERBAL MEDICINES; DISCRIMINATION; QUALITY; OILS; AUTHENTICITY; FRAUD; L.; Agriculture; Chemistry; Food Science & Technology